Zambia: Country brief - HarvestPlus (International Food Policy Research Institute, 2015)
HarvestPlus improves nutrition and public health in Zambia by promoting maize and orange sweet potato that provide more vitamin A in the diet. We work with more than 30 partners drawn from government, business, and civil society.